CRISPR/Cas9-Mediated Efficient Targeted Mutagenesis in Sesame (Sesamum indicum L.) - You, Jun; Li, Donghua; Yang, Li; Dossou, Senouwa Segla Koffi; Zhou, Rong; Zhang, Yanxin; Wang, Linhai (Frontiers in Plant Science, 2022)
The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system has been widely utilized for targeted genome modification in a wide range of species. It is a powerful genome editing technology, providing significant benefits for gene functional research and molecular breeding. However, to date, no study has applied this genome editing tool to sesame (Sesamum indicum L.), one of the most ancient and important oil crops used widely in diverse industries such as food and medicine. Herein, the CRISPR/Cas9 system along with hairy root transformation was used to induce targeted mutagenesis in sesame. Two single guide RNAs (sgRNAs) were designed to target two sesame cytochrome P450 genes (CYP81Q1 and CYP92B14), which are the key biosynthetic gene of sesamin and sesamolin, respectively. Sequencing data illustrated the expected InDel mutations at the target sites, with 90.63 and 93.33% mutation frequency in CYP81Q1 and CYP92B14, respectively. The most common editing event was single nucleotide deletion and insertion. Sequencing of potential off-target sites of CYP92B14-sgRNA showed no off-target events in cases of three mismatches. High-performance liquid chromatography analysis showed that sesamin and sesamolin biosynthesis was effectively disrupted in the mutated hairy roots, confirming the crucial role of CYP81Q1 and CYP92B14 in sesame lignan biosynthesis. These results demonstrated that targeted mutagenesis was efficiently created by the CRISPR/Cas9 system, and CRISPR/Cas9 coupled with hairy root transformation is an effective tool for assessing gene functions in sesame.